Peran Jaksa Dalam Pengawasan Narapidana Yang Diberikan Pelepasan Bersyarat Di Kota Surakarta (Studi Kasus Kejaksaan Negeri Surakarta) - Nidyaningrum, Anggy Anastasya, Dr. Natangsa Surbakti, S.H, M.Hum, Hartanto, S.H., M.Hum (2016)
This study aims to determine the role of the prosecutor in the supervision of prisoners granted conditional release, procedures and forms of supervision of the Prosecutor in supervising prisoners granted conditional release, and the goal was given conditional release for prisoners in the State Attorney Surakarta. This research method using juridical empirical approach, the type of data in the form of primary data, secondary data such as interviews and primary legal materials, secondary and tertiary. Data were collected by field studies and literature study with qualitative data analysis. The results showed that the role of prosecutor in the supervision of inmates granted release Conditional regulated in Law Number 14 Year 2004 on the Prosecutor of the Republic of Indonesia in Article 30 Paragraph (1), as for the procedure or form of supervision of the Prosecutor of the inmates who received Release of Conditional assigned by the Party Organization correctional by proposing at the Ministry of Justice as provided for in Article 15 Paragraph (1) Criminal Code and inspections carried out by the Prosecutor at the convict lived, whereas the main purpose given conditional release, so that prisoners could return to live in the community in good behavior.